Answer:
x = -2 , y = 3
Step-by-step explanation:
Solve the following system:
{13 + 2 x - 3 y = 0 | (equation 1)
12 + 3 x - 2 y = 0 | (equation 2)
Express the system in standard form:
{2 x - 3 y = -13 | (equation 1)
3 x - 2 y = -12 | (equation 2)
Swap equation 1 with equation 2:
{3 x - 2 y = -12 | (equation 1)
2 x - 3 y = -13 | (equation 2)
Subtract 2/3 × (equation 1) from equation 2:
{3 x - 2 y = -12 | (equation 1)
0 x - (5 y)/3 = -5 | (equation 2)
Multiply equation 2 by -3/5:
{3 x - 2 y = -12 | (equation 1)
0 x+y = 3 | (equation 2)
Add 2 × (equation 2) to equation 1:
{3 x+0 y = -6 | (equation 1)
0 x+y = 3 | (equation 2)
Divide equation 1 by 3:
{x+0 y = -2 | (equation 1)
0 x+y = 3 | (equation 2)
Collect results:
Answer: {x = -2 , y = 3